Les nations indiennes, source inattendue d’innovation - Marie-Claude Strigler (Revue LISA)
Economic development is usually conceived as the utilization and development of natural and human resources available to produce marketable goods and services which may be exchanged with other segments of society for other goods and services. Far from being fossilized societies, prisoners of their colonial past, Indian nations have always innovated in this domain, using their traditions to find new and original solutions to their economic problems, while securing their cultural identity. There is a renewal of Indian cultures whenever a tribe’s traditions and values are the basis of its development.